Psychosocial safety climate and self-efficacy: Moderating role of job-related expectations in Pakistani private-sector employees during the COVID-19 pandemic - Maqsood, Saira; Sohail, Marva; Naeem, Fatima; Nazri, Mohammad; Fatima, Deep (Frontiers in Psychology, 2023)
The labor force in Pakistan comprises 59.8 million individuals. The employees have faced major changes in work dynamics and psychosocial safety climate during the COVID-19 pandemic. The purpose of the current study is to find the relationship between psychosocial safety climate, self-efficacy, and job-related expectations. It explores the moderating role of job-related expectations on the relationship between psychosocial safety climate and self-efficacy. It was hypothesized that: there is likely to be a significant relationship between psychosocial safety climate, self-efficacy, and job-related expectations; job-related expectations are likely to moderate the relationship between psychosocial safety climate and self-efficacy, and there are likely to be differences between married and unmarried employees; men and women; satisfied and unsatisfied employees with respect to psychosocial safety, self-efficacy, and job-related expectations. Correlational research design and a convenience sampling strategy was used. 281 employees (M=30.74 years, SD= 10.99) of the private sector (including Educational, Industrial, and IT) organization during the COVID-19 pandemic were part of the study. Results show that psychosocial safety climate had a positive significant relationship with job-related expectations and self-efficacy. Job expectations also, significantly correlated with self-efficacy. There were significant differences on measures of study variables with respect to gender, marital status and employee satisfaction. This research has implications for administration, managers, policy makers, and organizational psychologists.